Using a large international sample to investigate epilepsy in Rett syndrome - Bao, X.; Downs, Jennepher; Wong, K.; Williams, S.; Leonard, H. (Wiley-Blackwell Publishing Ltd., 2013)
Aim The aim of this study was to identify characteristics of epilepsy in Rett syndrome (RTT), and relationships between epilepsy and genotype. Method Information on 685 females with RTT recruited to the international Rett syndrome database (InterRett) with a pathogenic MECP2 mutation was obtained from family and clinician questionnaires. Individuals with RTT were aged 1 year 4 months to 54 years 2 months (mean 11y 1mo; SD 9y 4mo). Results Among them, 61% had epilepsy, with half diagnosed by the age of 5 years. Those with a large deletion had the earliest median age at epilepsy onset and those with p.R133C the latest age at onset. The highest rate of active epilepsy (54%) was in those aged 12 to 17 years. Compared with those with a p.R133C mutation, active seizures were more likely to be reported in those with a large deletion (odds ratio 3.71; 95% confidence interval 1.13–12.17) or p.T158M (odds ratio 2.92; 95% confidence interval 1.04–8.20). Commonly used medicines included valproate (47%), carbamazepine (39%), lamotrigine (30%), levetiracetam (24%), and topiramate (19%). Interpretation Genotype influences the age at onset and severity of epilepsy in RTT. Large sample sizes as available through InterRett assist in understanding the complexity of epilepsy in RTT in relation to genotype.